Surgical rates in the era of biological therapy: up, down or unchanged?. Issue 4 (July 2017) - Olivera, Pablo; Spinelli, Antonino; Gower-Rousseau, Corinne; Danese, Silvio; Peyrin-Biroulet, Laurent
Abstract : Purpose of review: The aim of this review is to summarize data regarding surgical trends in inflammatory bowel disease in the prebiologic and biologic era, with a focus on population-based studies and randomized controlled trials (RCTs). Recent findings: There is paucity of data in RCTs regarding surgical rates, with only a few clinical trials reporting them. From the available data, meta-analyses of RCTs have concluded that antitumor necrosis α agents (anti-TNF) reduce surgical rates in ulcerative colitis and Crohn's disease. A large body of evidence from population-based studies from different regions of the world is available to evaluate surgical trends before and after the introduction of anti-TNF agents. The risk of surgery decreased significantly over the past six decades; these decreasing trends continued in the biologic era, which might indicate a potential beneficial disease-modifying effect of biologics. There is lack of data with nonanti-TNF biologics (i.e. anti-integrins and ustekinumab) regarding the risk of surgery. Summary: Although data from population-based studies and available RCTs suggest a protective effect from surgery of anti-TNF agents, definitive conclusions should be drawn only when more disease-modifying trials with different biologics and treatment strategies become available.